An exploration into the extent to whch French influenced the learning of English by Lebanese students in a French-medium school - Dalati, Sarah Abdelrahim (Beirut University of Balamand. Faculty of Arts and Social Sciences, department of English, 2008)
The researcher decided to conduct this piece of research in order to investigate a point made by many parents these days: English is easier to learn after French has been learnt rather than vice versa. The challenge facing the researcher, a former student from a French-medium background, was not to prove which language was better for the students to learn so that their parents could choose the appropriate school, but to explore the situation in which students learn a second foreign language (English) in a formal setting after both their native and first foreign language (French) have been learnt. A feature that immediately stood out when comparing the students questionnaires (Part I), where students indicate their attitudes towards six English skills/sub-skills on a five-choice-Likert-scale, was the tendency towards the middle point on the scale of ease/difficulty. It is of course human nature not to go for extremes; that is why people are expected to cluster. Students may not actually know or it might be that they do not have a strong opinion about the ease/difficulty of a given skill. There is obviously, not a great difference between easy/very easy or between difficult/very difficult, and to some extent these terms may have been considered virtually identical by the students. Another noticeable feature was the agreement among the students that the speaking skill was the easiest among all the skills/sub-skills. Another prominent feature in comparing the students questionnaires (Part II) was the tendency of the students to see writing as the language area most negatively influenced by the knowledge of the French language. Students of both classes agreed that writing is the second most difficult skill after listening. Part III of the questionnaire revealed many instances of French language use in a short English writing task, this confirming the previous finding that the writing skill needs to be given more thought in the respondent students English classes. Finally, the researcher noticed more interlingual than intralingual errors in the writing of the students and these resulted from French language transfer. After a two-week observation of two Grade 10 English classes, the researcher gained considerable insight into how the methodology used by the teachers was affecting the students. It was found that the teacher who awakened the students awareness towards language differences and similarities, developed a methodology more effective and successful than the other teacher who did less of the latter. Two major themes were identified from the teachers interview: a favorable learning environment in the English classes and the influence of background language knowledge. This project was conceived, and it is hoped that it represented a modest attempt to assess the impact of, firstly, knowledge of the French language and, secondly, teaching strategies/methodology upon the learning of English.
: Mémoire
Keywords: English Language Education Language of teaching; L enseignement de la Langue Anglaise Langue d enseignement